ESSENCE OF LEGAL RECOGNITION OF THE SMART CONTRACT IN THE LIGHT OF AMERICAN SOLUTIONS - Hulicki, Maciej (Człowiek w cyberprzestrzeni, 2020)
The article addresses blockchain and the smart contract technology based on it, which is important for the modern economy. It shows solutions that have been implemented in the United States, mainly at the state level. All of them give legal recognition to the use of smart contracts in trade. This authorization of blockchain technology and smart contracts triggers material legal consequences. Although smart contracts may be traded in business relations without specific legislative solutions, their introduction enhances the parties’ legal certainty and security of trade, and builds a stable platform for the development of this technology.